2019
DOI: 10.5624/isd.2019.49.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting modulation transfer function measurements in cone-beam computed tomographic images

Abstract: Purpose This study was designed to investigate the effects of voxel size, the oversampling technique, and the direction and area of measurement on modulation transfer function (MTF) values to identify the optimal method of MTF measurement. Materials and Methods Images of the wire inserts of the SedentexCT IQ phantom were acquired, and MTF values were calculated under different conditions (voxel size of 0.1, 0.2, and 0.3 mm; 5 oversampling techniques; simulated pixel loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, larger voxels do not always mean lower diagnostic accuracy. 30,31 Studies that have evaluated the influence of voxel size in diagnoses using cone beam computed tomography images of root fracture are conflicting. 31,32,33 Whereas a previous investigation showed significantly higher detection of vertical root fractures in images with smaller voxel size, 32 Özer 33 reported that there were no significant differences in the diagnostic accuracy of root fracture among cone beam computed tomography images captured with different voxel sizes.…”
Section: Discussionmentioning
confidence: 99%
“…However, larger voxels do not always mean lower diagnostic accuracy. 30,31 Studies that have evaluated the influence of voxel size in diagnoses using cone beam computed tomography images of root fracture are conflicting. 31,32,33 Whereas a previous investigation showed significantly higher detection of vertical root fractures in images with smaller voxel size, 32 Özer 33 reported that there were no significant differences in the diagnostic accuracy of root fracture among cone beam computed tomography images captured with different voxel sizes.…”
Section: Discussionmentioning
confidence: 99%
“…40 The smallest possible voxel size should preferably be used for scans of small structures in order to maximize the accuracy of the measurements. 18,21,41,42 However, higher-resolution scans require longer acquisition times, because they must collect more projections and generate large datasets. Therefore, the tradeoff between voxel size and scan time should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%